Overcome uncertainties of vertical take-off and landing aircraft based on optimal sliding mode control - Wajdi Sadik Aboud; Hayder S. Abd Al-Amir; Aseel A. Alhamdany; Fahad M. Kadhim (Institute of Advanced Engineering and Science, 2023)
This study aims to design a robust and optimal controller to overcome the problems related to the existence of disturbances and uncertainties during takeoff and landing operations of vertical take-off and landing (VTOL) aircraft. The dynamics are decomposed into two phase’s parts which are the minimum phase and the non-minimum phase. These two-part are controlled by proposing a robust nonlinear controller represented by sliding mode control (SMC). Also, the chattering effect due to the fast-switching surface in SMC is eliminated by utilizing a proposed sigmoid function which acts as the sigmoid function. The controller's main parameters are tuned optimally based on the particle swarm optimization (PSO) algorithm. In addition, the controller guaranteed the system stability based on the Lyapunov and Routh theories. The main output parameter responses represented by the positioning of the centre of mass and angle of rolling are determined with bounded control inputs. The performance of the proposed controller is tested by tracking VTOL parameters to the desired trajectories. The simulated results not only showed a significant tracking trajectory but also system stability guaranteed. In addition, the results showed an improved rate of 72% and 84% compared with those results obtained from the literature.